Rancangan Sistem Penilaian Kinerja Divisi Marketing Menggunakan Human Resource Analytic - Angela Caroline; Rio Fernando (Jurnal Manajemen dan Bisnis Kreatif, 2024)
Employees are the core of any successful business, and their skills are critical to achieving company goals. This research focuses on improving performance management in the sales and marketing department of Hotel BC. By carefully examining the core competencies of the sales and marketing team, this research aims to develop a performance evaluation system that accurately reflects employee contributions. This system will utilize the strengths of human resource information systems and data analysis. Our research used an analytical descriptive approach to understand the current performance evaluation process and identify areas for improvement. Preliminary findings indicate that work ethic, sales achievement, and company loyalty are important factors in assessing the performance of marketing staff. While these factors may evolve as the hotel develops, it is imperative to maintain a rigorous and systematic approach to performance evaluation.